Challenges Hampering Adoption of Different Housing Models to Access Housing by Households in Nairobi County - Kamande, Francis; Oboka, Wycliffe; Gweyi, Moses (European Journal of Business and Strategic Management, 2023)
Purpose: This study aimed to assess the challenges hindering the adoption of diverse housing models for household access to housing in Nairobi County, Kenya. Utilizing the Public Interest Economic Regulation Theory (PIERT), the Q Theory of Housing Investment, and the Theory of Distributive Justice, the research explores the interplay between government regulations, market forces, and social equity in the context of affordable housing. Methodology: Employing a descriptive research design, the study investigates the impact of housing regulations on housing access through mortgage and cooperative models. The research sample comprises 385 households, CEOs of housing financing organizations, and government officers. By analyzing the usage prevalence of housing models, the study delves into challenges such as high-interest rates, limited mortgage financing access, and insufficient awareness about housing options. The research employs a nuanced approach, considering the competitive dynamics within the housing sector and the need for equitable resource distribution. Findings: The study reveals that the mortgage model is most prevalent (41.4%), followed by the incremental model (28.0%) and cooperative model (23.7%). High-interest rates, restricted mortgage financing access, and inadequate awareness about housing options emerge as significant challenges hampering housing model adoption. Additionally, housing regulations, vital for safety, impact affordability, with 39.2% of respondents acknowledging this influence. Unique Contribution to Theory, Practice and Policy: This study contributes valuable insights to the existing body of knowledge by synthesizing the PIER, Q Theory of Housing Investment, and Theory of Distributive Justice. The study therefore validates these theories by offering a comprehensive understanding of the intricate interplay between regulations, market dynamics, and social equity in the adoption of affordable housing models. The recommendations, including lowering mortgage interest rates, enhancing financing access, promoting awareness about housing models, and fostering collaborative efforts among stakeholders, provide actionable strategies for policymakers, practitioners, and researchers to improve housing access in Nairobi County.